(Dis)integrated Care: Barriers to Health Care Utilization for Trans Women Living With HIV. (September 2017) - Munro, Lauren; Marshall, Zack; Bauer, Greta; Hammond, Rebecca; Nault, Caleb; Travers, Robb
Abstract : N/A: Transgender (trans) women have been particularly impacted by HIV. To seek insights into the dynamics of health service utilization, interviews were conducted with trans women living with HIV ( n = 14) as part of the Trans PULSE community‐based research project in Ontario, Canada. Service providers ( n = 10) were also interviewed to provide additional details about communication between trans women, social service providers, and clinicians. Results highlight how both problematic interactions with individuals and health systems navigation challenges affect access to services and impede the development of trans‐specific HIV supports. Participants described discrimination, identified strategies for navigating a dysfunctional system, and outlined specific ways in which health and social services may be failing trans women living with HIV. Findings support the importance of coordinating HIV services and transition‐related care, and providing training for service providers.